Analysis Of External And Internal Factors Of Nurse Turnover: A Systematic Review - Nurul Arifah; Mira Triharini; Andri Setia Wahyudi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: The nurse’s intention to leave the hospital was the settling problem in the hospital, because nurse turnover intention always occurs every year and may continue to increase if not handled. The reason for turnover was to a great extent slanted to the degree of occupation fulfillment, organizational factors, and threatening the workplace, bringing about an absence of inspiration to remain. Objective: to analyze external and internal factors of nurse turnover. Methods: Systematic review method used in this study on 15 scientific articles with limitations of publication time in 2016-2021. Four databases were included in this review such as Scopus, Ebsco, Pubmed, and ScienceDirect. Journals were selected based on predetermined criteria and a critical appraisal process was carried out. The Joanna Briggs Institute (JBI) Critical Appraisal tools were used to assess the bias study. Results: The results of the analysis of scientific articles were known that internal factors of nurse intention to leave were nurse age, education level, and job stress factors. While, an external factors that affect nurse intention to leave the hospital were work environment, job satisfaction, the relationship between nurse and manager, social support and organizational commitment. Conclusion: In conclusion, the factors that influence the turnover intention of nurses based on the results of a systematic review are job dissatisfaction and organizational factors.